DISTRIBUTION OF SURFACTANT AND PHENOL IN COASTAL WATERS OF JAKARTA GULF - Ermin K. Winarno; Winarti Andayani; Agustin Sumartono (Universitas Gadjah Mada, 2006)
The investigation of the anionic surfactant and phenol contamination in sea water of Jakarta Gulf was carried out. The sea water samples in Jakarta Gulf were collected in May 2004 at 21 stations (sampling sites). The monitoring results indicated that the anionic surfactants were detected in sea water samples from 20 stations with the low varied level from 0.276 mg/L to 0.779 mg/L. The anionic surfactant at the station 21 was detected with the highest value, it was 1.202 mg/L. The phenol pollutants in sea water samples from 16 stations were detected with higher level than permitted concentration for sea water, while the samples from 5 stations were not detected. The phenol concentration in sea water samples were varied from 0.009 mg/L to 1.364 mg/L.